From mitochondria to sarcopenia: role of 17β-estradiol and testosterone - Tian, Xu; Lou, Shujie; Shi, Rengfei (Frontiers in Endocrinology, 2023)
Sarcopenia, characterized by a loss of muscle mass and strength with aging, is prevalent in older adults. Although the exact mechanisms underlying sarcopenia are not fully understood, evidence suggests that the loss of mitochondrial integrity in skeletal myocytes has emerged as a pivotal contributor to the complex etiology of sarcopenia. The alterations in mitochondrial network involve impaired mitochondrial quality control (proteostasis, biogenesis, dynamics, and mitophagy), increased oxidative stress, accumulation of mtDNA damage, and activation of pro-apoptotic signaling pathways. Interestingly, a deficiency of sex hormones (e.g., 17β-estradiol and testosterone) has also been associated with sarcopenia. Indeed, 17β-estradiol (E2) and testosterone (T) targeted mitochondria and exhibited activities in regulating mitochondrial functions. In this review, the crosstalk among mitochondria, sex hormones, and sarcopenia will be discussed to elucidate the potential mechanism that E2 and T play in the onset of sarcopenia by regulating mitochondrial function in skeletal muscle.